The Transformation of Consumers Behavior: A Study Realised on Romanian Consumers - Olivia Doina NEGOIȚĂ; Mirona Ana Maria POPESCU; Ramona Mihaela BULBOACĂ (Communications of International Proceedings, 2020)
Understanding consumer motivation in online shopping is essential for a successful digital business. In a global online marketplace, competition is no longer limited to physical stores during business hours. Increasing competition, combined with the need for consumers to have a richer shopping experience, inevitably induce the need for retailers to rethink their online strategy. For many retailers, creating an online experience, enhanced by technologies such as 3D or virtual reality, is becoming at least as important as providing easy and personalized ordering, payment and delivery solutions. In this context, the definition of the consumer in the digital age leads to the realization and adaptation of online marketing strategies. The authors aim to present the main types of consumers, the factors that influence their behavior in order to achieve basic patterns. Based on the onset of the COVID 19 pandemic, this behavior has undergone changes due to a reconfiguration of consumer types. This aspect was illustrated by the authors by conducting a quantitative research through the questionnaire at the Romanian level.
Keywords: Consumer behavior; buying patterns; behavioral segmentation.